A rare case report of post-partum ovarian vein thrombosis after manual removal of placenta - Gohel, Deep K.; Mehta, Samir R.; Patel, Ankita; Borole, Supriya Y. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Post-partum ovarian vein thrombosis (POVT) is an uncommon diagnosis that may lead to morbidity or mortality if unrecognized. This report discusses a single case of POVT in our hospital, along with the treatment and clinical course. The mechanism is believed to be right-sided clot formation provoked by anatomical and hormonal changes of gestation. Diagnosis is challenging as most patients are previously healthy and symptoms are often vague. Although the differential is broad, modern imaging is sensitive and specific for diagnosis. Prompt treatment with broad-spectrum antibiotics and anticoagulation may reduce morbidity, and prognosis following treatment is excellent.